Intranasal Niosomal Gel for Brain Drug Delivery: A Promising Strategy for Quetiapine Fumarate Targeting - Kumar, Dinesh; Komal, Harish; Gulati, Puja (Journal of Neonatal Surgery, 2025)
Intranasal drug delivery has gained attention as a non-invasive approach to enhance brain targeting by bypassing the blood-brain barrier. Niosomal in situ nasal gels provide a promising platform for improving drug retention, mucoadhesion, and controlled release. Quetiapine fumarate, an atypical antipsychotic, suffers from poor oral bioavailability due to extensive first-pass metabolism. Chitosan-coated niosomal in situ nasal gels offer enhanced permeability, bio adhesion, and sustained drug release, ensuring efficient brain delivery. This review explores the formulation, characterization, and therapeutic potential of intranasal niosomal gels for brain drug delivery, with a focus on their pharmacokinetic advantages, challenges, and future prospects. The integration of nanotechnology with intranasal administration could revolutionize neuropsychiatric drug therapy, offering improved patient compliance and therapeutic efficacy.